Benchmarking the efficiency of domestic banks in Malaysia / Suraya Ahmad and Wan Noor Hazlina Wan Jusoh - Ahmad, Suraya; Wan Jusoh, Wan Noor Hazlina (Research Management Institute (RMI), 2012)
This study examines the relative efficiency of the nine Islamic subsidiaries and nine commercial banks in Malaysia from the year 2008 to 2010. To measure relative efficiency of the selected banks, the study applies the Data Envelopment Analysis in the analysis. The study adopts the intermediation approach in defining the inputs and outputs. The study selects personnel expenses and total customers deposits as inputs, while the output is total loans. This study found that the technical inefficiency of the selected banks in 2008 was due to the pure technical inefficiency. This indicated that the scale efficiency was higher than the pure technical efficiency. However, in 2009 and 2010, the pure technical efficiency was higher compared to the scale efficiency. Hence, the technical inefficiency was due to the scale inefficiency. Later, the study compares the efficiency of the Islamic subsidiaries and commercial banks using the independent sample t-test. The study found that there is no significant difference in the technical efficiency and pure technical efficiency level for Islamic subsidiaries and commercial banks. On the other hand, there is a significant difference in the scale efficiency level for both banks at p=0.014.